Evaluation of phenolic compounds, antioxidant and antiproliferative activities of 31 grape cultivars with different genotypes. Issue 6 (15th August 2018) - Xia, Lanlan; Xu, Changmou; Huang, Kunlun; Lu, Jiang; Zhang, Yali
Abstract: This study evaluated the total phenolic content, phenolic composition, antioxidant and in vitro antiproliferative properties of seeds and skins of 31 different grape cultivars. These properties of seeds and skins varied greatly among grape cultivars. European grapes had the highest values of phenolic compounds, antioxidant properties in seeds followed by Muscadine > American grapes > Oriental grapes. European grape seed extracts also were the strongest in inhibiting the growth of HepG2 cell, followed by American grapes > Muscadine > Oriental grapes. While these values of the Euro‐Asian or Euro‐American hybrids fell between the parents. However, the differences of these values in skin extracts among different grape cultivars were not significant. The antiproliferative activities were significantly correlated to the three antioxidant assays and the main phenolic compounds. Practical applications: This study presents phenolic compounds, antioxidant, and in vitro antiproliferative properties of seeds and skins of 31 different grape cultivars. The information is highly relevant to the ever‐increasing need for natural sources of antioxidants or nutraceuticals among consumers. The study also provides information for grape geneticists to breed cultivars with higher nutritional value, and for food scientists to exploit the natural polyphenol antioxidants in various grape pomace.